2022
DOI: 10.1371/journal.pgph.0000162
|View full text |Cite
|
Sign up to set email alerts
|

National trauma system establishment based on implementation of regional trauma centers improves outcomes of trauma care: A follow-up observational study in South Korea

Abstract: Although South Korea is a high-income country, its trauma system is comparable to low- and middle-income countries with high preventable trauma death rates of more than 30%. Since 2012, South Korea has established a national trauma system based on the implementation of regional trauma centers and improvement of the transfer system; this study aimed to evaluate its effectiveness. We compared the national preventable trauma death rates, transfer patterns, and outcomes between 2015 and 2017. The review of prevent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…The effectiveness of transport to trauma center was well-known from previous studies, 4 5 and studies in Korea have also shown that transport to trauma center can make better outcomes. 30 31 32 However, our study suggested that the transportation to the trauma center after severe trauma may not be significantly effective for pediatric populations. It is well validated that pediatric trauma centers improved clinical and functional outcomes for pediatric patients with traumatic injuries.…”
Section: Discussionmentioning
confidence: 68%
“…The effectiveness of transport to trauma center was well-known from previous studies, 4 5 and studies in Korea have also shown that transport to trauma center can make better outcomes. 30 31 32 However, our study suggested that the transportation to the trauma center after severe trauma may not be significantly effective for pediatric populations. It is well validated that pediatric trauma centers improved clinical and functional outcomes for pediatric patients with traumatic injuries.…”
Section: Discussionmentioning
confidence: 68%
“…Despite the lack of a solid foundation for trauma and injury research in the country, a few researchers have introduced and analyzed assessment tools such as AIS, ISS, RTS, and TRISS. 1 7 8 9 10 11 The establishment of the first RTC in Korea in 2004 marked a significant milestone, and the foundation for trauma research and care has gradually improved over the past decade. As the trauma center system reaches maturity, it is essential to analyze optimized datasets to improve the quality of care and assess the suitability of evaluation tools.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the overall incidence of GI cancer has been decreasing with an increase in screening tests [ 12 , 13 ]. In trauma, the blood transfusion rate is increasing, which is thought to be due to the establishment and systematization of trauma centers in Korea and active treatment for trauma patients [ 14 ]. In addition, the number of blood transfusions in hematologic diseases is increasing, which is thought to be due to the development of treatment, as well as the increased incidence [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%